Case report: Chronic disseminated intravascular coagulopathy with concurrent paraneoplastic secondary hyperfibrinolysis in a dog with metastatic nasal adenocarcinoma - Granger, Kyle L.; Paulos, Trish; Boss, Mary-Keara; Guieu, Liz; Shropshire, Sarah (Frontiers in Veterinary Science, 2024)
In human medicine, hemostatic disorders such as thrombocytopenia, hyperfibrinolysis, and disseminated intravascular coagulopathy (DIC) have been associated with many cancers. Acute hemorrhage secondary to hyperfibrinolysis has been predominantly reported with prostatic adenocarcinoma in human patients. To the author’s knowledge, severe bleeding due to paraneoplastic hyperfibrinolysis has not yet been reported in veterinary medicine. The case involves an 8-year-old neutered male Border Collie who was evaluated for progressive and recurrent epistaxis, having a history of one year of treatment for metastatic nasal adenocarcinoma. A progressive and severe coagulopathy thought to be related to the known cancer was diagnosed. Advanced coagulation testing was consistent with a chronic DIC and secondary hyperfibrinolysis. Throughout one week of hospitalization, the dog was treated with multiple blood products, vitamin K1, and anti-fibrinolytic medications. While the dog was initially discharged home, the dog re-presented the following day and was humanely euthanized due to a perceived poor quality of life. Post-mortem analysis revealed a histopathologic diagnosis of disseminated adenocarcinoma. In dogs with disseminated nasal adenocarcinoma that are experiencing severe bleeding, paraneoplastic secondary hyperfibrinolysis should be considered as a differential. Knowing this association could help guide treatment recommendations for optimal patient management.